2013
DOI: 10.21273/hortsci.48.7.855
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Improves Tomato Salinity Tolerance through Sodium Partitioning within the Shoot

Abstract: Two greenhouse experiments were carried out to analyze the shoot sodium (Na+) partitioning, yield, and fruit quality of ‘Cuore di Bue’, a salt-sensitive heirloom tomato (Solanum lycopersicum L.), ungrafted or grafted onto interspecific tomato hybrid rootstocks (S. lycopersicum × S. habrochaites) ‘Maxifort’ and ‘Arnold’ in 2009, ‘Arnold’ and ‘Armstrong’ in 2010, grown at different salinity stress (SS) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…'Beaufort', 'He-Man', and 'Resistar' grown under low to moderate salt-stress conditions had enhanced titratable acidity (TA), total soluble solids (TSS), and ascorbic acid concentrations in fruit, but grafting and rootstock choice had no effect on any quality characteristics. Di Gioia et al [14] reported similar results: fruit contents of TSS, TA, and dry matter were unaffected by grafting at any salinity level.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…'Beaufort', 'He-Man', and 'Resistar' grown under low to moderate salt-stress conditions had enhanced titratable acidity (TA), total soluble solids (TSS), and ascorbic acid concentrations in fruit, but grafting and rootstock choice had no effect on any quality characteristics. Di Gioia et al [14] reported similar results: fruit contents of TSS, TA, and dry matter were unaffected by grafting at any salinity level.…”
Section: Introductionmentioning
confidence: 63%
“…Grafted tomatoes may yield 30% more marketable fruit per plant, but their contents of vitamin C and total phenolics may decrease significantly as a result of grafting [13]. Di Gioia et al [14] found that vitamin C content decreased by 14-20% in the fruit of tomato plants grafted onto 'Beaufort F1' and 'Maxifort F1' compared with fruit of ungrafted plants. Savvas et al [15] investigated the effects on fruit yield and quality of grafting a commercial tomato hybrid onto three commercial tomato rootstocks grown in a recirculating hydroponic system.…”
Section: Introductionmentioning
confidence: 99%
“…), in the present study, we hypothesised that grafting tomato onto vigorous interspecific hybrids ( S. lycopersicum × S. habrochaites ), which have been demonstrated to be tolerant to salinity stress (Di Gioia et al . ), might raise tomato tolerance to excess B. Therefore, we investigated how grafted, self‐grafted and non‐grafted tomato plants, grown in hydroponic culture, respond to excess B (up to 15 mg·l −1 ) in terms of growth, B uptake and its partitioning in plant tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was reported that marketable yield increased in tomatoes with rootstock use [23,25,26]. For example, tomato cv.…”
Section: Parameters Of Yieldmentioning
confidence: 95%
“…The effect of rootstocks on the amount of TSS was found not statistically significant [23][24][25][26], although some researchers have observed that soluble solid content was lower in grafted compared to non-grafted plants [27][28][29].…”
Section: Introductionmentioning
confidence: 99%